Degenerative neuronal changes in the rat thalamus induced by status epilepticus at different developmental stages - Druga, Rastislav; Mares, Pavel; Otáhal, Jakub; Kubová, Hana (Epilepsy research, 2005)
SE was induced in Wistar rats at post-natal (P) days 12, 15, 18, 21, and 25 to determine distribution and severity of thalamic damage in relation to time after SE. Six different intervals from 4 h up to 1 week were studied using Fluoro-Jade B (FJB) staining. Severity of damage was semi-quantified for every age-and-interval group. Distribution of neuronal damage within various thalamic nuclei was mapped by a computer-aided digitizing system. A consistent neuronal damage occurred in functionally heterogenous thalamic nuclei. Damage was found in all age groups although its extension and time course as well as the number of involved thalamic nuclei varied. Number of injured thalamic nuclei rapidly increased with age on SE-onset. In P12 group, degenerating neurons were consistently seen in the mediodorsal and lateral dorsal thalamic nuclei. Since P15, neurodegeneration was observed additionally in midline, ventral and caudal thalamic nuclei (visual and auditory thalamic nuclei), in the lateral posterior and in the reticular nucleus. In P21 and P25 animals, the majority of thalamic nuclei exhibited marked neuronal damage. Nuclei with a small number (anterior and intralaminar) or no FJB-positive neurons (the ventral nucleus of the lateral geniculate body) were exceptional. The pattern of thalamic damage is age-specific; its extent and severity increases with age.
Keywords: Fluoresceins; chování zvířat; Thalamus; novorozená zvířata; věkové faktory; status epilepticus; počet buněk; krysa rodu Rattus; Time Factors; zvířata; neurony; barvení a značení; potkani Wistar; časové faktory; thalamus; Animals, Newborn; fluorescenční barviva; Fluorescent Dyes; Rats, Wistar; Male; fluoresceiny; degenerace nervu; organické látky; Organic Chemicals; Neurons; design s pomocí počítače; Computer-Aided Design; Rats; Age Factors; Animals; Status Epilepticus; mužské pohlaví; Behavior, Animal; Staining and Labeling; Nerve Degeneration; Cell Count